The influence of maternal anxiety and cortisol during pregnancy on childhood anxiety symptoms. (May 2022) - McGuinn, Laura A.; Tamayo-Ortiz, Marcela; Rosa, Maria José; Harari, Homero; Osorio-Valencia, Erika; Schnaas, Lourdes; Hernandez-Chavez, Carmen; Wright, Rosalind J.; Klein, Daniel N.; Téllez-Rojo, Martha Maria; Wright, Robert O.
Abstract: Background: The etiology of child and adolescent anxiety remains poorly understood. Although several previous studies have examined associations between prenatal maternal psychological functioning and infant and child health outcomes, less is known about the impact of maternal anxiety specific to pregnancy and cortisol during pregnancy on childhood anxiety outcomes. Methods: Participants included 496 mother-child pairs from the PROGRESS longitudinal birth cohort in Mexico City. Anxiety symptoms were assessed at age 8–11 years during 2018–2019 using the Revised Children's Manifest Anxiety Scale. Pregnancy-specific anxiety was assessed using an expanded version of the Pregnancy Anxiety Scale. Maternal biological stress response during pregnancy was assessed using salivary cortisol measures (area under the curve, cortisol awakening response, and diurnal slope). Linear regression models were used to estimate associations between maternal anxiety and cortisol in relation to continuous child anxiety symptom T-scores. Models were adjusted for maternal age, socioeconomic status, child sex and age, and gestational age at saliva collection. Results: We found that higher levels of pregnancy-specific anxiety in the mother were associated with higher anxiety symptoms in the child (β: 1.30, 95% CI: 0.19, 2.41). We additionally observed an association between higher maternal total cortisol output during pregnancy and higher anxiety symptoms in the child (β: 1.13, 95% CI: 0.25, 2.01). Discussion: These findings highlight the importance of screening for maternal pregnancy-specific anxiety and the need to identify interventions and support for mothers during pregnancy in order to promote healthy outcomes for mothers and their children. Highlights: The etiology of child and adolescent anxiety remains poorly understood. We studied impacts of maternal cortisol and anxiety on offspring anxiety symptoms. Maternal pregnancy-specific anxiety was associated with anxiety in the child. Higher maternal prenatal cortisol was related to greater childhood anxiety symptoms. These findings highlight the importance of screening for pregnancy-specific anxiety.